Effectiveness of architectural and planning solutions in inclusive educational environment for children with autism spectrum disorders - Elena Yu. Strelnikova; Olga N. Chebereva (Архитектура, строительство, транспорт)
Creating inclusive educational environments in schools is a pressing issue today, yet its practical implementation remains limited to a few schools. This work draws upon a review of Russian and international theoretical literature outlining the requirements and recommendations regarding architectural space, design, functional relationships, and the typology of specialized classrooms for educating children with ASD. Considering these requirements, the authors analyzed the architectural-environmental, spatial-planning, and functional-technological solutions for implementing an inclusive educational environment, as piloted at School No. 96 "Eureka-Development named after Nagibin M. V." (Rostov-on-Don). The advantages identified include: the availability of multiple classrooms capable of accommodating over 40 children; the multipurpose use of spaces; the use of both specialized and standard furniture and equipment; the integration of environmental elements to support special education needs (therapeutic pedagogy) within the classroom structure; and the possibility of holding inclusive events in school-wide facilities. Disadvantages identified include the lack of several essential rooms; the division of the inclusive unit across two floors; compromised classroom functionality due to reduced floor space per student; and unclear functional zoning within classrooms. Based on the literature reviewed, the following improved spatial planning solutions were proposed: creating a dedicated resource area featuring a broader range of specialized classrooms and support spaces; locating the entire inclusive unit on the ground floor; reorganizing the school’s entrance area; installing an elevator to facilitate access for individuals with limited mobility; and considering the addition of an integrated, attached building unit.